Gender, Latar Belakang Sosio-ekonomi Keluarga, dan Prestasi Akademik Mahasiswa (Kasus pada Universitas Islam Negeri Terbesar di Kalimantan) - Juhaidi, Ahmad (Metta : Jurnal Ilmu Multidisiplin, 2023)
Student academic achievement is not only determined by learning factors in the classroom. Gender, family socioeconomic, and cultural capital of students affected academic achievement. Studies on these variables still need to be carried out in Islamic College (PTKI) context. Therefore, this study aims to verify gender relations, family economic background, parents' education level, students' cultural capital, and academic achievement. This research is field research with quantitative-comparative and correlational approaches. The study participants amounted to 174 students of Antasari State Islamic University. Participants were assigned convenience and snowballing sampling. Data was collected using questionnaires disseminated online through Whats App messages. Data analysis of research results using the Mann-Whitney you Test and Spearman Rank-Order Correlation with the help of SPSS version 27. Research findings prove that female and male academic achievement differences are statistically significant (Asymp. Sig. <0.05). This study indicates that gender significantly affects student academic achievement at PTKI. In addition, correlational statistical analysis proved that pocket money, Single Tuition Fee (UKT), and the education level of fathers and mothers were not related to student academic achievement (Asymp. Sig.>0.05). In contrast, students' cultural capital has a significant relationship with students' academic achievement (Asymp. Sig.<0.05). However, the correlation between the two variables is either very weak or negligible (ρ = 0.210). The results of this study indicate that high cultural capital will significantly increase student academic achievement. This research makes a conceptual contribution to the influence of gender and the relationship between socioeconomic background, family and cultural capital on student academic achievement in the field of Islamic Studies in the context of PTKI.